2020
DOI: 10.3390/nu12030838
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Intake of One-Carbon Metabolism Nutrients in the Year before Pregnancy and Birth Anthropometry

Abstract: Few studies have evaluated the role of methylation-pathway nutrients involved in fetal growth (B vitamins, choline, betaine, and methionine). These one-carbon metabolism (OCM) nutrients are essential for DNA methylation in the periconception period. We aimed to characterize dietary patterns of 1638 women from the EDEN mother-child cohort in the year before pregnancy according to the contribution of OCM nutrients and to study the association of such patterns with anthropometric measurements at birth. Dietary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
1
17
1
1
Order By: Relevance
“…Previous work in adults has shown that supplementation of dietary choline and betaine led to decreased visceral fat accumulation, waist circumference, and body weight which suggests they may contribute to the development of chronic disease [32,33]. However, limited studies exist in children investigating their role, and findings in adults remain inconsistent [32,[34][35][36]. Children get ready to enter the school environment at six years of age and experience more independence to self-select and manage their own food menu choices [37].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in adults has shown that supplementation of dietary choline and betaine led to decreased visceral fat accumulation, waist circumference, and body weight which suggests they may contribute to the development of chronic disease [32,33]. However, limited studies exist in children investigating their role, and findings in adults remain inconsistent [32,[34][35][36]. Children get ready to enter the school environment at six years of age and experience more independence to self-select and manage their own food menu choices [37].…”
Section: Introductionmentioning
confidence: 99%
“…The diet of women during the year before pregnancy was assessed retrospectively at inclusion (before 28 weeks' gestation; 15 weeks on average) by using a validated food-frequency questionnaire (13). A food composition database was not available to estimate the direct intake of some nutrients of interest (methionine, choline and betaine), so we used different sources to establish a food composition database and calculated individual nutrient intake following a methodology that we previously described (11). Three dietary patterns -"varied and balanced", "vegetarian tendency", and "bread and starchy food"were identified using the reduced rank regression method to characterize OCM micronutrient intake (folates, choline, betaine, methionine, vitamins B2, B6, B12) in the year before pregnancy (14).…”
Section: Dietary Data and Other Information Collected During Pregnancymentioning
confidence: 99%
“…The "vegetarian tendency" pattern was characterized by high coefficients for vitamin B6, B9 and betaine to the detriment of other nutrients such as vitamin B12, choline, and methionine. The "bread and starchy food" pattern was mainly characterized by a high coefficient for betaine and negative coefficients for vitamins B2, B6, and B9 (11). The main characteristics of the patterns are presented in Table 1.…”
Section: Dietary Data and Other Information Collected During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Usia reproduktif yaitu 20-35 tahun berhubungan dengan kemampuan tubuh untuk menyerap nutrisi dalam tubuh secara optimal sehingga ibu hamil dapat memiliki status gizi yang baik dan bermanfaat bagi bayi untuk pemenuhan nutrisi (Ogundipe et al, 2012). Status gizi ibu hamil juga dikaitkan dengan pengetahuan ibu, pengetahuan terkait nutrisi ibu hamil menjadi salah satu faktor yang berpengaruh terhadap status gizi ibu hamil, salah satu cara yang dapat dilakukan untuk meningkatkan pengetahuan dengan mengikuti kegiatan penyuluhan kesehatan ibu hamil sehingga ibu tahu terkait nutrisi yang baik sebelum dan sesudah kehamilan (Lecorguillé et al, 2020).Berdasarkan uraian latar belakang diatas peneliti tertarik untuk penelitian tentang analisis faktor determinan status gizi ibu hamil di momby kids Jombang.…”
Section: Pendahuluanunclassified